Epizooties et géographie du commerce du bétail dans la Corne d’Afrique - Géraldine Pinauldt (EchoGéo)
Livestock exports to the middle eastern countries, all along the 20th century, have organised society and territory of the northern somali region. During the 90's, this system has been challenged by both political turmoils in the whole horn of africa region, and a severe sanitary ban on livestock exports imposed by the middle eastern countries. Exports through Berbera, the former main livestock port, have seriously decreased, for the benefit of emerging Djibouti and Bosaaso. Sanitary certification, system in which quarantine station in association with recognized veterinary services  is a core element, is today's only key to the middle eastern markets, especially to Saudi Arabia, the main importer. To get a chance to regain those lucrative markets, the States involved in livestock exports are trying to obtain recongnized quarantine stations. This «quarantine war » is the visible aspect of tranformations taking place in livestock market chain and in the territories of this trade.